Empowerment of Fishery Products in an Islamic Economic Perspective: Strategies to Increase Fishermen's Income - Baharuddin, Agusman; Wargo (Zabags International Journal of Economy, 2025)
This study aims to analyze the practice of empowering fishery products of the Lambur Luar Village community in increasing fishermen's income based on an Islamic economic perspective. Using a descriptive qualitative approach, data was obtained through interviews and direct observation. The results of the study show that fishermen still depend on the sale of raw products to middlemen, with low added value. In the perspective of Islamic economics, empowerment should include aspects of justice, productivity, and distribution of benefits. Therefore, sharia-based strategies are needed such as strengthening cooperatives, access to halal financing, and education in seafood processing. The conclusion of this study emphasizes the importance of integrating Islamic values in the economic empowerment of coastal communities.